Siting assessment for Kinetic Energy Turbines: an emplacement study for sea and river applications. (December 2017) - Zupone, G. Lo; Massaro, S.; Barbarelli, S.; Sulpizio, R.
Abstract: The siting and design of a Tidal Energy Converter (TEC) require the characterization of the flow velocity field acting in terms of space and time, in order to assess the hydrodynamic forces, to calculate the structural loading and power capacity, also helping investment strategy and project financing. In this framework, the selection of the emplacement site is of paramount importance for optimizing efficiency of TEC. In this study, we propose site assessment procedures for emplacement of TEC machines, comparing a sea tidal site with two rivers ones. Sites differ each other from geomorphological characteristics. The Cook Inlet (South-Central Alaska) is a large subarctic estuary, which extends about 250 km from Anchorage bay to the Pacific Ocean. Tidally dominated currents control the hydrographic regime, with water levels and currents periodically influenced by tides from the Gulf of Alaska, which are significantly amplified as approaching Anchorage bay. The Cháng Jiāng river (also named Yangtze, China) is the longest in Asia and the third in the world, with a huge flow rate. The Pearl River Estuary (China) has a length of about 70 km, a width of about 15 km and an average depth of about 4.8 m. It is deeper than 20 m in its eastern part, and discharges into a microtidal environment along the northern shelf of the South China Sea. The TEC performances have been compared in the three different geomorphological environments. Results show how TEC in rivers can perform up to 5.47 kW/m 2, a huge value compared to the wide sea turbines, able to perform up to 10.76 kW/m 2 .